Characterization and origin of the 'B' and 'C' compounds in the acid/neutral forensic signatures of heroin – products from the acylation of porphyroxine and subsequent hydrolysis. Issue 3 (23rd November 2015) - Casale, John F.; Casale, Ellen S.; Toske, Steven G.; Hays, Patrick A.; Panicker, Sini
Abstract : Two significant compounds often found in the gas chromatographic analysis of the acid/neutral extracts from illicit heroin have remained uncharacterized for 30 years. The unknown compounds are referred to as the 'B' and 'C' compounds. It has been postulated that these compounds arise from acetylation of porphyroxine, a rhoeadine alkaloid found at trace levels in the opium poppy, Papaver somniferum . Porphyroxine was isolated from opium and acetylated to produce N, O 8 ‐diacetylporphyroxine. Mild hydrolysis produced N, O 8 ‐diacetyl‐O 14 ‐desmethyl‐ epi ‐porphyroxine (the C compound) and N‐acetyl‐O 14 ‐desmethyl‐ epi ‐porphyroxine (the B compound). Both N, O 8 ‐diacetyl‐O 14 ‐desmethyl‐ epi ‐porphyroxine and N‐acetyl‐O 14 ‐desmethyl‐ epi ‐porphyroxine were determined to be C‐14 epimers of porphyroxine and N, O 8 ‐diacetylporphyroxine. The non‐epimerized isomers of the B and C compounds were also detected in illicit heroin, but at much lower levels. Chromatographic and spectroscopic data are presented for the aforementioned compounds. The presence/absence and relative concentrations of these compounds is presented for the four types of heroin (Southwest Asian, South American, Southeast Asian, and Mexican). The prevalence of detection for the B and C compounds are Southwest Asian = 92‐93%, South American = 64‐72%, Southeast Asian = 45‐49%, and Mexican ≤  3%. When detected, the overall trend of relative concentrations of dicaetylporhyroxine, the B‐compound, and C‐compound is Southwest Asian > South American > Southeast Asian, each by an order of magnitude. These compounds were rarely detected in Mexican heroin. The presence/absence and relative concentrations of these compounds provide pertinent forensic signature characteristics that significantly enhance the final regional classifications. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Porphyroxine was acetylated and then hydrolyzed to indentify several unknown impurities found in the acid/neutral signatures of heroin.